2013
DOI: 10.1519/jsc.0b013e3182764945
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Performance of Lateral Cutting Maneuver From Lateral Sliding and Hip Extension and Abduction Motions, Ground Reaction Force, and Body Center of Mass Height

Abstract: Basketball players have to move laterally and quickly change their movement directions, especially during defensive moves. This study aimed to investigate how frontal and sagittal plane hip movements relate to fastness and quickness of lateral cutting maneuvers from sliding. Three-dimensional biomechanical data were obtained for 28 female college basketball players while they performed lateral cutting maneuvers using their left leg after 2 lateral sliding steps. The lateral cutting index (LCIndex) expressing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
3
20
0
1
Order By: Relevance
“…The amount of force expressed in the medio-lateral direction in particular (i.e. the direction of intended travel) is most likely to result in improved CODS performance (Shimokochi, Ide, Kokubu, & Nakaoji, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of force expressed in the medio-lateral direction in particular (i.e. the direction of intended travel) is most likely to result in improved CODS performance (Shimokochi, Ide, Kokubu, & Nakaoji, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6 Great jump height and quick sprint actions are expected to take an advantage over opponents, higher propulsive forces are also reported to correlate with better sports performance. [7][8][9] Previous studies showed higher plantar pressures and shear forces in the medial forefoot region during propulsion in typical basketball manoeuvres (e.g. sprinting, jumping, and side-cutting) when compared with running.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of the present study is that the results show that the CODD can be used to quantify COD ability during a sharp cutting task, which often is more widely observed in field and court sports such as basketball (15), American football (6), netball (18), soccer (3) and rugby union (7). The 90° cut task used in the present study revealed large correlations to linear sprint performance (5, 10 and 20 m).…”
Section: Discussionmentioning
confidence: 61%
“…The emphasis an assessment has on COD speed declines the longer the test, becoming more reliant on anaerobic capacity and sprint ability, as more time is spent running between COD actions (12). For instance, typical test durations for the T-test, Illinois, L-Run and Pro-Agility are 8-12 seconds (11,19), [14][15][16][17][18] seconds (19), 6-8 seconds (5,16) and 4-5 seconds (13,16), respectively. Therefore, performance on all of these tests may be influenced by metabolic limitations (19) and sprint ability (12) and less on COD ability.…”
Section: Introductionmentioning
confidence: 99%